2020
DOI: 10.1111/liv.14601
|View full text |Cite
|
Sign up to set email alerts
|

Liver histopathology in severe COVID 19 respiratory failure is suggestive of vascular alterations

Abstract: SARS2‐CoV‐2 breakout in Italy caused a huge number of severely ill patients with a serious increase in mortality. Although lungs seem to be the main target of the infection, very few information are available about liver involvement, possibly evocating a systemic disease. Post‐mortem wedge liver biopsies from 48 patients died from severe pulmonary COVID‐19 disease with respiratory failure were collected from two main hospitals in northern Italy. No patient had clinical symptoms of liver disease or signs of liv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
291
9
16

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(352 citation statements)
references
References 15 publications
17
291
9
16
Order By: Relevance
“…While we cannot exclude these findings being meaningful (if they are present throughout the entire liver), we do not believe that vascular injury is the major mechanism of injury in the liver in COVID-19 patients. This contrasts with a case series from Italy, which describes vascular pathology not frequently encountered in our cohort [18]. The "thrombotic bodies" we observed are likely the same "microthrombi" identified in multiple organs in a recent series of seven autopsies [19].…”
Section: Discussioncontrasting
confidence: 99%
“…While we cannot exclude these findings being meaningful (if they are present throughout the entire liver), we do not believe that vascular injury is the major mechanism of injury in the liver in COVID-19 patients. This contrasts with a case series from Italy, which describes vascular pathology not frequently encountered in our cohort [18]. The "thrombotic bodies" we observed are likely the same "microthrombi" identified in multiple organs in a recent series of seven autopsies [19].…”
Section: Discussioncontrasting
confidence: 99%
“…Recent research has shown that the hypercoagulable state of COVID-19 patients alters intrahepatic vascular structures and causes a variable degree of luminal thrombosis. This may add to other mechanisms of liver damage in COVID-19 patients (19).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown that, in addition to coagulation dysfunction, COVID-19 patients will have different degrees of liver damage as well. The pathogenesis of liver damage complicated by COVID- 19 is not yet clear; however, current mainstream views on the mechanism of liver injury include: (1) Angiotensin-converting enzyme 2 (ACE2) mediates SARS-CoV-2 invasion of target cells. Bile duct epithelial cells highly express ACE2, and its expression level is similar to alveolar type II cells, which is the main target cell type of SARS-CoV-2 in the lung.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of this phenomenon correlates with the severity of the critical illness of the patients. Postmortem series have confirmed evidence of multi-organ and disseminated microvascular thrombosis in various organs [ 19 , 20 ]. This has served as a platform for a few ongoing clinical trials to try prophylactic high-intensity prophylaxis in critically ill patients with COVID-19 with no known thrombosis.…”
Section: Thrombosis and Hemostasis And Covid-19mentioning
confidence: 99%